(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Osteoarticular infection of humerus and shoulder joint are uncommon. Prompt diagnosis and management of acute osteoarticular infection with early antibiotic and sometimes surgery is required to prevent chronic osteomyelitis and sequalae of septic arthritis. This case illustrates how a treatable case of acute osteoarticular infection was missed and progressed to chronic osteomyelitis. The aim of reporting this case is to present a rare site of osteoarticular infection of humerus and shoulder joint was complicated due to failure in recognition and management